A User-Friendly Wearable Telerehabilitation System Based on Neuromotor Training for Mild Post-Stroke Patients: The DoMoMEA System - A. Zedda; M. Caruso; S. Bertuletti; G. Baldazzi; G. Sedda; A. Spanu; D. Riboni; A. Pibiri; M. Monticone; A. Cereatti; D. Pani (IEEE Access, 2025)
Home-based telerehabilitation technologies can support the long-term rehabilitation needs of post-stroke patients. This work describes an Android-based wearable system for telerehabilitation (DoMoMEA), which engages such patients in a full-body customized neuromotor rehabilitation protocol. DoMoMEA features seven inertial units and five force sensors, which capture patient’s body posture, movements, and interactions with a non-immersive virtual reality environment, providing real time scores, motivational feedback, and online automatic corrections for performance errors. Clinically relevant parameters can be collected and sent to a remote server where they can be retrieved by a physiotherapist through a dedicated web application, according to a store-and-forward telemedicine approach. Clinicians can also personalize the training settings to ensure a high level of engagement and challenge for patients, based on their residual motor abilities, needs and progress. Preliminary tests performed on 11 healthy elderly volunteers revealed a high usability of the system ( $82~± ~6$ points in the System Usability Scale questionnaire). Furthermore, the system was presented to experienced physiatrists and physiotherapists, who provided their assessment by a semi-structured interview. The evidence underscored the usefulness of DoMoMEA not only at home, but also in daily clinical practice.